A Theoretical Approach for Understanding the Haze Phenomenon in Bottled White Wines at Molecular Level - Toledo, L.N.; Salazar, F.N.; Aquino, A.J.A. (South African Journal of Enology and Viticulture, 2017)
The stabilisation of the proteinaceous material in the wine matrix represents one of the big challenges for the production of quality white wines, but the characterisation of the mechanism that governs the interactions between its components is still a very challenging goal. The aim of this study was to provide new information for developing new technologies in the stabilisation of bottled white wines using a novel theoretical approach. This method combines electronic structure calculations for the determination of the a stable conformation of three ligands that may interact with one of the proteins responsible for the haze in wines, the thaumatin-like protein (TLP), with the search for the mode of binding between this protein and its ligands through docking calculations. The result shows that sites that exposed positive residues to the surface of the protein are the sites favoured for the caffeic acid (CA) binding. Additionally, it was observed that the ligand with the lowest binding energy (-7.38 kcal/mol) was the quercetin (Q). The presence of a Ï€-Ï€ stacking interaction with the residue F118 is confirmed in a family of TLP-Q complexes, and it is proposed that the mechanism of haze formation in white wines during bottle storage seems to be related to the interaction of polyphenolic molecules with some residues of this big cavity; these residues or sites of interaction can be considered as future targets in the control of the haze phenomena and in the research on alternatives to the fining treatment in the wine industry.